2014
DOI: 10.1155/2014/767312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Moisture Deficit Stress on Biomass Accumulation of Four Coffee (Coffea arabica) Varieties in Zimbabwe

Abstract: A study was conducted to evaluate four common coffee (Coffea arabica) varieties in Zimbabwe for drought tolerance and ability to recover. The plants were subjected to drought stress for 21 and 28 days with evaluation of recovery done 14 days after interruptive irrigation. Coffee varieties were not significantly different in initial fresh and dry biomass before stressing (P>0.05). CR95 had significantly accumulated more (P<0.05)dry root mass (0.8 g) than the rest of the varieties after 21 days of drought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
2
10
0
1
Order By: Relevance
“…The shoot to root ratio of trees shifted with age, generally from the 4:1 (one-year-old) assumed for tropical trees to 2:1 (Van Noordwijk et al 2002). In the present study, about 75.76−84.43% of the dry matter of the coffee plants come from aboveground, similar to one-year-old arabica coffee (Chemura et al 2014). In addition, it was found that N is the most important factor influencing the growth and photosynthesis of C. arabica plants, followed by K, while P has the least influence on adult plants (Cai et al 2004).…”
Section: Discussionsupporting
confidence: 67%
“…The shoot to root ratio of trees shifted with age, generally from the 4:1 (one-year-old) assumed for tropical trees to 2:1 (Van Noordwijk et al 2002). In the present study, about 75.76−84.43% of the dry matter of the coffee plants come from aboveground, similar to one-year-old arabica coffee (Chemura et al 2014). In addition, it was found that N is the most important factor influencing the growth and photosynthesis of C. arabica plants, followed by K, while P has the least influence on adult plants (Cai et al 2004).…”
Section: Discussionsupporting
confidence: 67%
“…The results of this research are in line with that of Mohammed et al (2018) which state that drought stress for 28 days (4 weeks) causes a significant difference in the growth of Robusta coffee plants, and this could be seen more clearly in the variable of total dry weight of plants. Similar findings are also found in Arabica coffee seedlings, namely 21 days of drought stress causes significant differences in plant biomass accumulation (Chemura et al, 2014).…”
Section: Seedling Growthsupporting
confidence: 73%
“…Stress of soil moisture on Robusta coffee plant decrease plant growth, plant biomass, fruit production, number of intact grains, three group of coffee grains, and increase the amount of the empty beans (DaMatta and Ramalho, 2006;Sumirat, 2008;Chemura et al, 2014). The biological properties of Robusta coffee grown under the shade is one of the characteristics of Robusta coffee that makes the coffee plant takes up the organic material from the litter into the soil and affects to the content of the humic substances in the soil (Baon dan Wibawa, 2005;Souza et al, 2012;deAlcantara-Notaro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%